Pengaruh Kualitas Produk, Harga, dan Lokasi terhadap Keputusan Pembelian (Studi pada Rumah Makan “Mie Gacoan” di Daerah Istimewa Yogyakarta) - Evi Okta Fiana; Retno Hartati (Cakrawangsa Bisnis: Jurnal Ilmiah Mahasiswa, 2022)
This study aims to determine the effect of product quality, price, and location on purchasing decisions on gacoan noodles in the Special Region of Yogyakarta. The sampling method used non-probability sampling with a purposive sampling method. The number of samples used in this study were 126 respondents. The data analysis methods used are validity test, reliability test, normality test, t test, heteroscedasticity test, multicollinearity test, multiple linear regression analysis, the goodness of fit test, coefficient of determination adjusted R square. The results of this study indicate that product quality and price have no effect on purchasing decisions, in contrast to location which has a positive effect on purchasing decisions on gacoan noodles in the Special Region of Yogyakarta. Adjusted R² of 0.46 or 46% which means product quality, price, and location contribute 46% to the purchasing decision variable, while the remaining 54% is explained by other variables that are not included in this study.